Penerapan Suku Bunga Bank Indonesia sebagai Instrumen Utama Kebijakan Moneter di Indonesia Perspektif Ekonomi Islam ala Syafruddin Prawiranegara - Syah, Toufan Aldian; Aziz, Jamal Abdul (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2020)
Monetary policy is a factor that greatly determines the economic conditions of a country. Because it is very closely related to various things of economic activity in the efforts to achieve economic development that provides welfare for the community. This paper seeks to analyze the mechanisms of monetary instruments in Indonesia. Second, look at the extent of the implementation of monetary policy mechanisms in Indonesia by using Bank Indonesia Interest Rates. Third, the views of one of the Islamic economic leaders namely Sjafrudin Prawiranegara regarding the prohibition of the use of interest rates in Islam. Based on the analysis and discussion described above, the researcher concludes that the mechanism of interest rate-based monetary policy instruments in Indonesia remains the main instrument in controlling the country's economics and cannot be directly considered contrary to Islamic principles.